1963
DOI: 10.1002/ardp.19632960805
|View full text |Cite
|
Sign up to set email alerts
|

Arginin als Vorstufe von Galegin in Galega officinalis L. Zur Biochemie und Physiologie von Galegin in Galega officinalis L., III. Mitt.

Abstract: Archiv der R e u t e r Pharmazie 516 siert. Ausbeute 2,91 g = 99%. Orange-rote Kristalle, leicht loslich in Chloroform, loslich in Ather und Athano]. Schmp. 213-214'. N 18,46 Ketazin I V 2,38 g I (0,Ol Mol) werden in einem Gemisch von 6 ml 80proz. Hydrazinhydrat, 20 ml Eisessig und 30 ml Athano1 gelost und 15 Min. am RuckfluD zum Sieden erhitzt. Nach dem Erkalten wird das Reaktionsprodukt mit Wasser ausgefiillt und mehrmals aus Athanol / Wasser umkristallisiert. Ausbeute 0,94 g = 40%. WeiDes Kristallmehl, leic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the Medieval period, it was used as a therapy for diabetes (20,22). One of the main components of G. officinalis is alkaloid galegine possessing hypoglycemic properties in animal models (23). Furthermore, it was shown that G. officinalis has a remarkable effect on body weight loss and insulin (24).…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%
“…In the Medieval period, it was used as a therapy for diabetes (20,22). One of the main components of G. officinalis is alkaloid galegine possessing hypoglycemic properties in animal models (23). Furthermore, it was shown that G. officinalis has a remarkable effect on body weight loss and insulin (24).…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%
“…According to our results, the serum glucose level significantly decreased in treadmill exercise groups. In this context, M Rahmati et al showed that exercise on the treadmill reduced blood surge (30). The comparison of serum insulin levels in different groups showed that STZ-induced diabetes caused damage to pancreatic beta cells and reduced blood insulin levels (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the serum glucose level significantly decreased in treadmill exercise groups. In this context, G. Reuter et al showed that exercise on the treadmill reduced blood surge [34]. The comparison of serum insulin levels in different groups showed that STZ-induced diabetes caused damage to pancreatic beta cells and reduced blood insulin levels [32,35].…”
Section: Plos Onementioning
confidence: 99%